2020
DOI: 10.1182/bloodadvances.2020002642
|View full text |Cite
|
Sign up to set email alerts
|

Integrin VLA-4 as a PET imaging biomarker of hyper-adhesion in transgenic sickle mice

Abstract: In sickle cell disease (SCD), very late antigen-4 (VLA-4 or integrin α4β1) mediates the adhesion of reticulocytes to inflamed, proinflammatory endothelium, a key process in promoting vaso-occlusive episodes (VOEs). We hypothesized that a radionuclide tracer targeting VLA-4 could be harnessed as a positron emission tomography (PET) imaging biomarker of VOEs. We tested the VLA-4 peptidomimetic PET tracer 64Cu-CB-TE1A1P-PEG4-LLP2A (64Cu-LLP2A) for imaging hyper-adhesion–associated VOEs in the SCD Townes mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…16,17 Therefore, we hypothesized that the large iron deposits in SS-Selp 2/2 mice are the result of dysregulated iron clearance, secondary to impaired recruitment of myeloid cells in absence of P-selectin. Interestingly, we 11 have previously reported that the circulating myeloid cells (neutrophils and monocytes) are significantly elevated in SS-Selp 2/2 mice, 11,18 most likely because of impaired recruitment to tissues and bone marrow. Indeed, we found significant reduction in messenger RNA (mRNA) and expression of myeloid cell markers (Ly6G, CXCR4, CD62L, and CD11b) in the liver of SS-Selp 2/2 than SS mice (Figure 2E), which was further confirmed by the reduction in immunofluorescence staining for neutrophil marker (Ly6g) in SS-Selp 2/2 compared with SS liver (Figure 2F).…”
Section: Resultsmentioning
confidence: 85%
“…16,17 Therefore, we hypothesized that the large iron deposits in SS-Selp 2/2 mice are the result of dysregulated iron clearance, secondary to impaired recruitment of myeloid cells in absence of P-selectin. Interestingly, we 11 have previously reported that the circulating myeloid cells (neutrophils and monocytes) are significantly elevated in SS-Selp 2/2 mice, 11,18 most likely because of impaired recruitment to tissues and bone marrow. Indeed, we found significant reduction in messenger RNA (mRNA) and expression of myeloid cell markers (Ly6G, CXCR4, CD62L, and CD11b) in the liver of SS-Selp 2/2 than SS mice (Figure 2E), which was further confirmed by the reduction in immunofluorescence staining for neutrophil marker (Ly6g) in SS-Selp 2/2 compared with SS liver (Figure 2F).…”
Section: Resultsmentioning
confidence: 85%
“…A decrease in VLA‐4 expression on reticulocytes in SCD subjects treated with HC, a therapy known to reduce the clinical severity of SCD, was previously reported 32 . Recent positron emission tomography data indicate VLA‐4‐mediated hyper‐adhesion, primarily of SCD reticulocytes, during VOCs in the SCD Townes mouse model 33 . We have demonstrated that pulsatile flow increased VCAM‐1 – VLA‐4 adhesive interactions as compared to non‐pulsatile flow, 34 likely due to an increase in interaction time allowing for the development of additional adhesive points of attachment 5 .…”
Section: Introductionmentioning
confidence: 78%
“…Blood cell adhesion to the vascular endothelium is a crucial event in the pathophysiology of VOCs and other clinical manifestations of SCD [19]. VCAM-1/VLA-4 and P-Selectin/PSGL-1 interactions were reported as both independently and cumulatively contributing to risks of vaso-occlusive events [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Blood cell adhesion to the vascular endothelium is a crucial event in the pathophysiology of VOCs and other clinical manifestations of SCD [19]. VCAM-1/VLA-4 and P-Selectin/PSGL-1 interactions were reported as both independently and cumulatively contributing to risks of vaso-occlusive events [18, 20]. High levels of VLA-4 and VCAM-1 have been associated with vaso-occlusive adhesive events and severe disease phenotypes, and with a response to SCD-modifying therapy [21-26].…”
Section: Discussionmentioning
confidence: 99%